KAJIAN KOMPARATIF PERILAKU NETIZEN ASIA DAN EROPA PADA BISNIS ONLINE - B, Pamela Felita (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
This analysis a conceptual analysis. The purpose of this studywas to the difference netizens in asia and europe. Asia and Europe havedifferent levels of netizens. netizens in Asia increased higher comparednetizens in Europe. most netizens asia and europe use the buying and selltransaction via smartphone or tablet. Asia is a strong market potential inonline business, while in Europe there are several countries that are stillweak in the social networks and services delivery. China, Jepang, Korea,and Asia Tenggara a potential market of Asia, while German, Polandia,Norwegia is a potential market of EuropeKeywords : Netizen, Business Online